Fluid collection after distal pancreatectomy: a frequent finding - Tjaden, Christin; Hinz, Ulf; Hassenpflug, Matthias; Fritz, Franziska; Fritz, Stefan; Grenacher, Lars; Büchler, Markus W.; Hackert, Thilo (HPB, 2016)
Background - Fluid collections (FC) at the resection margin of the pancreatic stump after distal pancreatectomy (DP) are common radiological findings in follow-up scans. No recommendations exist regarding the management of such findings. The aim was to characterise incidence, risk factors, clinical impact and therapy of FC. - Method - Data of 209 patients who underwent DP between 07/2009 and 06/2011 were prospectively collected and analysed, regarding follow-up CT or MRI scan findings of FC at the resection margin. FC was defined as a cyst-like lesion >1 cm in diameter. - Results - A follow-up with at least two cross-sectional images was available in 159/209 patients. In the first postoperative control, 68 patients showed an FC (43%). FC size was classified as <5 cm (n = 38 pat.), 5-10 cm (n = 24 pat.) and >10 cm (n = 6 pat.). 20 patients (30%) showed clinical symptoms. Six patients (9%) required specific treatment, all other FC showed spontaneous regression. No correlation with stump closure techniques or preceding postoperative pancreatic fistula was found (4/68 patients, 6%). Multivariate analysis revealed standard resections as the only significant factor for FC. - Conclusions - FCs at the resection margin after DP are frequent and harmless findings. Therapeutic interventions are required in only 9% of all FC patients.
Gesehen am 27.05.2020